Radioembolization in the Treatment of Neuroendocrine Tumors of the Pancreas - John, Preethi K; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic neuroendocrine tumors (pNET) are a rare malignancy. Many patients will present with metastatic disease most commonly to the liver. Currently the standard of care for treatment of liver metastases from neuroendocrine tumors (NETs) is surgical resection. However, only few patients are candidates for surgical resection and require alternative options. Given the rarity of this disease; data regarding treatment options are minimal. In this paper, we will review data presented at the annual meeting of ASCO 2014 about the Survival following Y90 radioembolization for neuroendocrine tumor liver metastases (Abstract #e15166). This abstract shows evidence for survival benefit with the use of radioembolization in the treatment of metastatic neuroendocrine tumors to the liver. Image: Tufts Medical Center. Boston, MA, USA